Significance of environmental sustainability to maintain financial stability: mediating roles of financial inclusion - Arsalan Haneef, Malik; Mohamad, Jais; Shafinah, Rahim; Awais Ur, Rehman; Shahzeb, Khalid (Springer Link, 2023)
This study examined the impact of environmental sustainability on financial inclusion and financial stability in Asian countries over the period of 2009–2011. Composite variables representing environmental sustainability, financial inclusion and financial stability were constructed through principal component analysis using a variety of indicators. For conceptual foundation, stakeholder theory was applied, and the association between variables was analyzed using a generalized moment estimation method. Moreover, contrary to previous studies using limited indicators, this study used a wide range of vital indicators to measure environmental sustainability. The findings indicated that a sustainable environment fosters financial stability by reducing risks to financial institutions and increasing financial inclusion. Furthermore, financial inclusion partially mediated environmental sustainability and financial stability. The findings were robust according to different robust checks. Based on the results we conclude that if Asian governments are determined to improve financial stability and inclusion, they need to focus on environmental sustainability related to demand management. No prior study has shown that an enhanced sustainable environment increases financial inclusion and stability.